CONCEPTUAL MODEL FOR QUALITY ASSURANCE IN HIGHER EDUCATION - Dalia Susnienė; Gediminas Sargūnas; Laszlo T. Koczy (Taikomieji tyrimai studijose ir praktikoje, 2019)
There is a considerable pressure on higher education for a substantial improvement in its performance. Efforts in this direction are hindered by the lack of an agreed model for quality assurance. The aim of this paper is to present a general view and a brief literature review of the main aspects related to quality assurance in higher education and present a common framework for quality assurance at HEI. The proposed holistic model for quality assurance in higher education can serve as the ideal to address the service, education and implementation aspects synergistically.